Biomassa aérea em serras do semiárido brasileiro: Influência da altitude e estrutura das comunidades vegetais - Rêgo, Lucia Virginia Castor do (2017)
The Caatinga is considered a Tropical Dry Forest, being one the largest semiarid areas of the world locating in the Northeast region of Brazil. However, the investigations are scarce about the biomass and stock carbon for these areas, mainly testing the importance of forest attributes and environmental drives, in higher altitude areas, for example in highland areas. The aboveground biomass (AGB) and stock carbon were quantified for two highland areas in the Caatinga and related to possible drives factors, structural, altitude, individuals number, species richness, rarefiel richeness, Shannon diversity (H’), Equability by Pielou (J’) and environmental (altitude). Were realized performed liner mixed models (GLM), by means of subsets regression to test two alternative hypotheses, niche complementary and vegetation quantity. The highlands contribute (AGB) values higher than those quantified in other non – highlands Caatinga environments, however, higher values of AGB have been found in other ecosystems in Brazil. This increase in AGB correlates with the rarefiel richness of species and individuals numbers. Therefore, support was found for both hypotheses in the conduction of biomass to highlands in the semiarid. Diversity and density have positive effects for production of AGB in environments with richness lower than humid forest ecosystems. The higher altitude environments in the Brazilian semiarid are habitats that deserve attention so that, more research can be conducted, since, are areas that accumulate higher values of AGB in Caatinga. In addition, it is necessary to implement strategies of conservation by means of political measures, of the highland ecosystems in the Brazilian semiarid.